2015
DOI: 10.2147/ijn.s89156
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets in arthritis and recent trends in nanotherapy

Abstract: Due to its severity and increasing epidemiology, arthritis needs no description. There are various forms of arthritis most of which are disabling, very painful, and common. In spite of breakthroughs in the field of drug discovery, there is no cure for arthritis that can eliminate the disease permanently and ease the pain. The present review focuses on some of the most successful drugs in arthritis therapy and their side effects. Potential new targets in arthritis therapy such as interleukin-1β, interleukin-17A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 106 publications
2
5
0
Order By: Relevance
“…A study in rats showed that chitosan/hyaluronic acid gel injections delay the progression of osteoarthritis and lessen the pain in surgically induced knee osteoarthritis model in rats. These results support other published results, indicating an ameliorative effect of chitosan on human and rabbit osteoarthritis …”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…A study in rats showed that chitosan/hyaluronic acid gel injections delay the progression of osteoarthritis and lessen the pain in surgically induced knee osteoarthritis model in rats. These results support other published results, indicating an ameliorative effect of chitosan on human and rabbit osteoarthritis …”
Section: Introductionsupporting
confidence: 93%
“…Some of the drugs also made it to clinical trials, including aptamer−lipid NPs. 17,18 So far, carbohydrate NPs, such as those studied in this project, have shown low toxicity and high bioavailability. 19 Hyaluronic acid, a component of our aptamer NP (AN), is being used daily as an intra-articular injection in osteoarthritis with systemic distribution.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Current pathophysiological concepts acknowledge OA as a disease of the whole joint. Changes in the subchondral bone are a hallmark in the progression of OA and bone formation is locally imbalanced leading to the growth of osteophytes 9,10 . In OA, osteophyte formation is of clinical significance: Later stage osteophytes are suggested as a source of pain.…”
mentioning
confidence: 99%